ANALISIS VARIANS DALAM PENERAPAN STANDARD COSTING UNTUK PENGENDALIAN BIAYA PRODUKSI - Cindy, Joelion Winelia; Isnaniati, Siti; Athori, Agus (Jurnal Ilmiah Cendekia Akuntansi; Vol 7 No 4 (2022): Oktober, 2022)
ABSTRACT Production quality control is very important in ensuring the success of the production process. One of the The company is engaged in the plywood industry in its operations expecting maximum profit oriented with the lowest possible cost. For that required sacrifice costs. One of the cost control tools that can be used is standard costs. Standard costs are costs that are determined in advance, which is the amount of costs that should be incurred to make one unit of product. The purpose of the study was to determine the amount of difference between the standard costs set and the actual costs. The approach used in this research is descriptive quantitative. Interview data collection techniques and documentation. The data analysis technique in this study uses analysis of variance on production costs. The conclusion of the research based on the applied standard costs can make a comparison of the actual production costs and can know the deviations that occur in production costs. There is a profitable difference in 2021 of IDR 48,016,040 with this, the company should take corrective actions to support controlling production costs, the company can evaluate the previous period to be used as a guide for the next period. Keywords: Standard Cost, Analysis of Variance, Control